Investigation of arenavirus and filovirus infections in rodents and non-human primates in the United Kingdom - Onianwa, Okechukwu (2018)
Recent years have witnessed virus disease outbreaks that have caused considerable morbidity and mortality. As 80% of human viruses are zoonotic, outbreaks can be prevented by active surveillance of wildlife for pathogens with a potential for cross-species transmission. Rodents serve as important reservoirs for many zoonoses and epizooses. In this thesis, a cDNA library of 976 rodents, shrews, moles and birds was constructed. Molecular methods using inosine-containing degenerate primers were developed for the screening of novel viruses of the families, Arenaviridae and Filoviridae. Filovirus RNA was absent in all specimen screened. Lymphocytic choriomeningitis mammarenavirus (LCMV) RNA was detected in 4 Mus musculus (19%). Further screening of specimens obtained from a zoo outbreak resulted in the detection of LCMV RNA in a total of 20 M musculus, 2 Geoffroy’s marmoset, 1 black and white colobus and 1 Black-crested gibbon from two separate sampling sample sets. Viral RNA was detected in non-human primates (NHP) not previously reported. Rodents screened at the zoo after the outbreak were negative for LCMV RNA. Phylogenetic analyses of full-length glycoprotein precursor (GPC) of 4 NHP-derived and 4 rodent-derived LCMV revealed a clustering of the former with other lineage-I LCMV GPC sequences. Molecular characterisation of the novel LCMV strains uncovered a consistency in amino acid substitutions across primate-derived and rodent-derived LCMV strains at position 211 of GPC which may be a possible determinant for cross-species transmission. Analysis of the alpha-dystroglycan receptor of rodents and NHPs revealed residues that might influence GPC binding affinity and therefore drive virus evolution. Pseudoviruses constructed from GPC of rodent-derived LCMV displayed higher infectivities in hepatocellular carcinoma cells than their NHP-derived LCMV counterpart which is indicative of the existence of another unidentified host receptor. Together, the results establish a framework for further investigation of the molecular basis for cross-species transmission of LCMV between rodent and primate hosts.